Efektivitas Digital Marketing Berbasis Influencer dalam Promosi Produk Umrah di Media Sosial Instagram (Studi pada PT. Rayyah Arga Anugrah Kota Bengkulu) - Sabrina Aulia Salsabilla; Supardi Mursalin; Evan Stiawan (Universitas Muhammadiyah Surabaya, 2026)
The development of digital technology has encouraged Umrah travel agencies to implement social media–based marketing strategies. Instagram has become one of the most effective platforms for promoting Umrah services. This study aims to analyze the implementation of digital marketing and the effectiveness of influencer-based digital marketing at PT Rayyah Arga Anugrah in Bengkulu City. This research employs a descriptive qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. The research informants consisted of six individuals, including management or marketing staff of PT Rayyah Arga Anugrah, influencers who collaborate with the company, and Umrah pilgrims as service users. Data analysis was conducted qualitatively through data reduction, data presentation, and conclusion drawing. The results indicate that PT Rayyah Arga Anugrah has implemented digital marketing by utilizing Instagram as its main promotional medium. The strategies include managing informative and consistent visual content and collaborating with credible influencers. Influencer-based digital marketing is considered effective in strengthening branding, expanding promotional reach, and building trust among prospective pilgrims, which has a positive impact on increasing interest in Umrah registration.